An e‐Reporting Tool for Facilitating Submission of Veterinary Adverse Drug Reaction Reports - Heather Davies; Steven Smyth; Gina Pinchbeck; Munir Pirmohamed; Roy Savory; P. J. Noble; David Killick (Journal of Veterinary Internal Medicine)
ABSTRACT Background Adverse events (AEs) are under‐reported in veterinary medicine. The ability to report AEs directly from the practice management system (PMS) has been suggested to facilitate reporting. The Small Animal Veterinary Surveillance Network (SAVSNET) informatics system provides an opportunity to integrate reporting into the workflow such that reports can be submitted directly to the National Competent Authority, the Veterinary Medicines Directorate (VMD). Objectives Develop an AE reporting form linked to the PMS allowing for pre‐population of some fields from the electronic health record (EHR). Analyze the quality of submitted reports. Animals Animals attending United Kingdom (UK) first‐opinion veterinary practices participating in SAVSNET. Methods An AE “reporting button” was developed and available in the normal clinical workflow for SAVSNET enrolled practices using the Robovet PMS. The button facilitated capture of pertinent information relating to AEs, including the ability to append clinical notes from the associated EHR. After submission, reports were automatically submitted daily to the VMD. Report quality was assessed using an adapted version of the vigiGrade scoring system, which was used to compare the quality of reports submitted to the VMD via standard routes to those submitted via SAVSNET. Assessment of reports submitted via SAVSNET, was conducted twice. First, considering only information contained in the report and second, considering information contained in both the report and associated clinical notes. Results Sixty reports were submitted during the first 18 months by 42 different veterinary practices. The quality of SAVSNET reports was significantly improved by information contained within the clinical notes. These reports were more likely to be well‐documented than those submitted via standard routes. Conclusions and Clinical Importance Adverse event reports populated using EHR data are well documented and can support efficient reporting of AEs in veterinary medicine.